Efficacy and safety of oncolytic virus combined with chemotherapy or immune checkpoint inhibitors in solid tumor patients: A meta-analysis - Liu, Xiangxing; Zhang, Jiaojiao; Feng, Keqing; Wang, Simin; Chen, Liming; Niu, Suping; Lu, Qian; Fang, Yi (Frontiers in Pharmacology, 2022)
Background: In recent years, several clinical trials focused on oncolytic virus (OVs) combined with chemotherapy or immune checkpoint inhibitors (ICIs) in solid tumor patients, which showed encouraging effects. However, a few studies concentrate on the summary on the safety and efficacy of the combined treatments. Therefore, we conducted this meta-analysis to explore the safety and curative effect of the combined therapy. Methods: We searched in the PubMed, Cochrane Library, Embase and Clinicaltrials.gov to comprehensively select articles on OVs combined with chemotherapy or ICIs for the solid tumor treatment. Overall survival (OS), progression-free survival (PFS), 1-year survival rate, 2-year survival rate, objective response rate (ORR) and adverse events (AEs) were the outcomes. Results: 15 studies with 903 patients were included in this meta-analysis. The pooled ORR was 32% [95% confidence interval (CI): 27%-36%, I2=24.9%, p = 0.239]. Median OS and median PFS was 6.79 months (CI: 4.29-9.30, I2=62.9%, p = 0.044) and 3.40 months (CI: 2.59-4.22, I2=0.0%, p = 0.715), respectively. 1-year survival rate was 38% (CI: 0.29-0.47, I2=62.9%, p = 0.044) and 2-year survival rate was 24% (CI: 12%-37%, I2=0.0%, p = 0.805). The most common AEs were fever (63%, CI: 57%-69%, I2=2.3%, p = 0.402), fatigue (58%, CI: 51%-65%, I2=49.2%, p = 0.096), chill (52%, CI: 43%-60%, I2=0.0%, p = 0.958), neutropenia (53%, CI: 47%-60%, I2=0.0%, p = 0.944). Conclusion: OVs combined with ICIs showed a better efficacy than OVs combined with chemotherapy, which lends a support to further clinical trials of OVs combined with ICIs. Additionally, OVs combined with pembrolizumab may exert better safety and efficacy. Toxicity of grade ≥ 3 should be carefully monitored and observed. However, high-quality, large-scale clinical trials should be completed to further confirm the efficacy and safety of OVs combined with ICIs.